Nonconstant Harmonic Functions on the Level 3 Sierpinski Gasket (Analysis in Theory and Applications, 2014)
We give a detailed description of nonconstant harmonic functions on the level 3 Sierpinski gasket. Then we extend the method on $β$-set with $1/3< β < 1/2$.
Keywords: Nonconstant harmonic function; level 3 Sierpinski gasket; $β$-set.